The legal facets of a subalternized man Colonial Alagoas, 1755 - Campos Mendonça, Anne Karolline (Revista Crítica Histórica, 2018)
The following case was based on the observation of the protagonism of individuals that were considered inferior within the hierarchical logic of Old Portuguese Regime. Starting from a point of view on the conception and execution of Justice, the present text seeks to understand the mechanisms of the use of rights that surrounded those who did not have privileges. For this purpose, he look over, more emphatically, the request of Lázaro Coelho de Eça, made around 1754. Son of a captain of the village who longed to command, Lázaro was placed in the position of overseas subject, despite the vigor of political and social thought that forcibly and violently removed him from the paths that were desired to him. His application will not be analyzed here by the sturdy micropower strand, but rather will be at odds with the current historiographical trend. The focus of this work is precisely to interact with the reality of this individual who, conceiving possibilities of "negotiation" with the monarch, gave movement to a judicial framework that apparently benefited him, when in fact he led him to the basic functions of Justice, serving more specifically the objectives of social groups that considered themselves superior. Keywords: Colonial Alagoas, Justice, subalternized characters.